Sustentabilidade nos negócios financeiros: a relação entre a política de responsabilidade socioambiental do Banco do Brasil e as pequenas e médias empresas tomadoras de empréstimos - Matias, Damião Tiburtino (2009)
This dissertation entitled "Sustainability in the financial business: the relationship between the policy of social responsibility of the Bank of Brazil and small business borrowers for loans," has as main objective to analyze how the Bank of Brazil evaluates and monitors programs whose goal is sustainability, because, 200 years to complete, the Bank reaffirms its trajectory for greater promotion of development of the country, combining economic growth in its business to sustainable development. Thus, it is a literature search / exploration on the topic in question. Then a case study, supplemented by a field research - qualitative. Due to the treatment given by the authors investigated in relation to social context of sustainability, and corporate social responsibility, we could understand the importance to be given by all segments of society (including small, medium and large companies) on the conservation and / or environmental preservation, the respect and appreciation for human dignity, the distribution of income in a fair, quality of employment, equality in access to resources and social services and sociocultural diversity. As for the case study, regarding the evaluation and monitoring of projects with values equal to or greater than $ 10 million, emphasized the importance of the commitments made by the public, emphasizing, in this case, for the Equator Principles as marked important for social projects, structured financing. It is also the engagement of the Bank of Brazil with the principles of social responsibility, which is part of its eatratégia. For the field research, you can see the involvement of officials in the processes of evaluation and monitoring of risks in the operations sociaombintais / loans to small and medium enterprises lending policy and the ways that the Bank uses to assess and monitor the social and environmental risk